The relationship between the Baraitot in the Tosefta and their talmudic parallels. The evidence of tractate Berachot - Katzoff, Binyamin (Hebrew Union College annual / Jewish Institute of Religion, 2004)
It is generally thought that there is a close affinity between the baraitot in the Tosefta and their parallels in the Talmud of the Land of Israel, certainly a much closer affinity than that between the baraitot in the Tosefta and their parallels in the Babylonian Talmud. However, a close examination of linguistic and stylistic characteristics of parallel baraitot reveals that beside passages where the Tosefta preserves a more original version of the text than the parallels in both Talmuds, there are many others where we surprisingly find in the Tosefta linguistic and stylistic characteristics common to the Bavli. Two explanations of this phenomenon are: 1. the tannaitic sources were transmitted by the Babylonian tradents accurately and conservatively; 2. the language of the Tosefta, in both its manuscript recensions, was revised significantly while transmitted in a time and place when the Bavli exerted crucial influence on the transmission of talmudic texts. The scholarly investigation of rabbinic literature is apparently not sufficiently advanced yet to allow for a clear choice between the two possibilities, which would necessitate renewed investigation of many talmudic questions.